Exposure to nature is associated with decreased functional connectivity within the distress network: A resting state EEG study - Imperatori, Claudio; Massullo, Chiara; De Rossi, Elena; Carbone, Giuseppe Alessio; Theodorou, Annalisa; Scopelliti, Massimiliano; Romano, Luciano; Del Gatto, Claudia; Allegrini, Giorgia; Carrus, Giuseppe; Panno, Angelo (Frontiers in Psychology, 2023)
Introduction Despite the well-established evidence supporting the restorative potential of nature exposure, the neurophysiological underpinnings of the restorative cognitive/emotional effect of nature are not yet fully understood. The main purpose of the current study was to investigate the association between exposure to nature and electroencephalography (EEG) functional connectivity in the distress network. Methods Fifty-three individuals (11 men and 42 women; mean age 21.38 ± 1.54 years) were randomly assigned to two groups: (i) a green group and (ii) a gray group. A slideshow consisting of images depicting natural and urban scenarios were, respectively, presented to the green and the gray group. Before and after the slideshow, 5 min resting state (RS) EEG recordings were performed. The exact low-resolution electromagnetic tomography (eLORETA) software was used to execute all EEG analyses. Results Compared to the gray group, the green group showed a significant increase in positive emotions (F1; 50 = 9.50 p = 0.003) and in the subjective experience of being full of energy and alive (F1; 50 = 4.72 p = 0.035). Furthermore, as compared to urban pictures, the exposure to natural images was associated with a decrease of delta functional connectivity in the distress network, specifically between the left insula and left subgenual anterior cingulate cortex (T = −3.70, p = 0.023). Discussion Our results would seem to be in accordance with previous neurophysiological studies suggesting that experiencing natural environments is associated with brain functional dynamics linked to emotional restorative processes.